Results of the Cologne Corona Surveillance (CoCoS) study - a cross-sectional study: survey data on risk factors of SARS-CoV-2 infection in adults - Max Oberste; Nadja Schnörch; Kija Shah-Hosseini; Teodora Asenova; Felix Dewald; Clara Lehmann; Michael Buess; Gerd Fätkenheuer; Florian Klein; Kerstin Daniela Rosenberger; Annelene Kossow; Florian Neuhann; et al. (BMC, 2023)
Abstract Background The personal, environmental, and behavioral risk factors that play an important role in the spread of SARS-CoV-2 are still largely unclear. At the same time, there is limited evidence on the effectiveness of specific countermeasures for SARS-CoV-2. As a first approach to these questions, we use data from the Cologne Corona Surveillance (CoCoS) study, a large cross-sectional study conducted in Cologne, Germany, in June 2021. Methods This study was conducted in Cologne, Germany. Six thousand randomly selected Cologne residents who were 18 years of age or older were invited to participate in this study. Participant information was obtained via an online survey. Previous SARS-CoV-2 infections were recorded using self-reports. Sociodemographic and environmental information such as age, sex, living situation were collected. Potential SARS-CoV-2 risk behaviors were captured (workplace situation, adherence to hygiene regulations, and regular use of public transportation). Adherence to hygiene regulations was surveyed by determining the compliance with the 'AHA'-rules (German acronym that stands for keeping a distance of 1.5 m from fellow citizens, hand disinfection, and wearing a face mask). Binary logistic regression analysis was used to identify risk factors for SARS-CoV-2 infection. Results A sample of 2,433 study participants provided information. Comparison of the sample with the general population showed representativeness for most sociodemographic characteristics with a preference for higher level of education in the study sample. Younger age, as well as living with minor children (under 18 years) in the same household were associated with a higher number of self-reported SARS-CoV-2 infections. Adherence to hygiene regulations was associated with fewer self-reported SARS-CoV-2 infections in adults. Gender, size of living space per person, workplace situation (work from home versus working with contact to colleagues/customers), and regular use of public transportation showed no significant association with self-reported SARS-CoV-2 infections in multivariable analysis. Conclusion The presented results provide initial indications of which sociodemographic and behavioral factors may be associated with SARS-CoV-2 infection. However, the fact that these factors were recorded without exact dates and could have changed accordingly during the pandemic or after infection limits the strength of the results. Trial registration DRKS.de, German Clinical Trials Register (DRKS), Identifier: DRKS00024046, Registered on 25 February 2021.